2009
DOI: 10.4049/jimmunol.0901807
|View full text |Cite
|
Sign up to set email alerts
|

HOXB4-Transduced Embryonic Stem Cell-Derived Lin−c-kit+ and Lin−Sca-1+ Hematopoietic Progenitors Express H60 and Are Targeted by NK Cells

Abstract: Embryonic stem (ES) cells are a novel source of cells, especially hematopoietic progenitor cells that can be used to treat degenerative diseases in humans. However, there is a need to determine how ES cell-derived progenitors are regulated by both the adaptive and innate immune systems post transplantation. In this study, we demonstrate that hematopoietic progenitor cells (HPCs) derived from mouse ES cells ectopically expressing HOXB4 fail to engraft long-term in the presence of NK cells. In particular, the H6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
(46 reference statements)
0
30
0
Order By: Relevance
“…The in vivo NK activity was found to be increased and the frequency of teratoma formation significantly reduced (Dressel et al, 2010). In vivo rejection of murine ESC derivatives by NK cells has also been reported in Rag2 -/-mice (Tabayoyong et al, 2009). Both mouse models lack functional lymphocytes and contain greatly increased numbers of NK cells (Tabayoyong et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The in vivo NK activity was found to be increased and the frequency of teratoma formation significantly reduced (Dressel et al, 2010). In vivo rejection of murine ESC derivatives by NK cells has also been reported in Rag2 -/-mice (Tabayoyong et al, 2009). Both mouse models lack functional lymphocytes and contain greatly increased numbers of NK cells (Tabayoyong et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…In vivo rejection of murine ESC derivatives by NK cells has also been reported in Rag2 -/-mice (Tabayoyong et al, 2009). Both mouse models lack functional lymphocytes and contain greatly increased numbers of NK cells (Tabayoyong et al, 2009). The impact of NK cells in immunocompetent hosts might, however, be less important.…”
Section: Discussionmentioning
confidence: 94%
“…These CTLs were used as effector cells, whereas iPS-HPCs, M23e immortalized B cells, and M28e cells were used as target cells in 4-hour 51 Cr-release assay, as described previously. 25 …”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Indeed, our studies recently showed that NK cells regulated the engraftment of mouse ESC-HPCs. 25 Here, we studied the MHC expression by iPS-HPCs, iPSCs, and the parental fibroblasts. ESCs, ESC-HPCs, and UCB-CD34 1 cells…”
Section: Ips-hpcs Poorly Express Hla Moleculesmentioning
confidence: 99%
See 1 more Smart Citation